Cobalt(III)-Catalyzed Diastereoselective Three-Component C–H Bond Addition to Butadiene and Activated Ketones - Shen, Zican; Li, Chen; Mercado, Brandon Q.; Ellman, Jonathan A. (Synthesis, 2020)
A highly diastereoselective three-component C–H bond addition across butadiene and activated ketones is described. This transformation provides homoallylic tertiary alcohols through the formation of two C–C σ-bonds and with complete selectivity for an E-alkene isomer. The reaction exhibits good scope with respect to activated ketone inputs, including highly strained cyclic and electron-deficient cyclic and acyclic ketones. Additionally, high diastereoselectivities were achieved for alcohols prepared from unsymmetrical ketones.
Keywords: C–H activation; cobalt; ketones; diastereoselectivity; multicomponent reaction; homogeneous catalysis